Immune system stimulation induced by porcine reproductive and respiratory syndrome virus alters plasma free amino acid flux and dietary nitrogen utilization in starter pigs1. (10th April 2019) - McGilvray, Whitney D; Klein, David; Wooten, Hailey; Dawson, John A; Hewitt, Deltora; Rakhshandeh, Amanda R; De Lange, Cornelius F M; Rakhshandeh, Anoosh
Abstract: Changes in plasma free amino acid (AA) flux reflect the modification of AA metabolism in different metabolic states. Infectious diseases repartition AA away from protein retention toward processes involved in immune defense, thus impacting AA utilization in pigs. The current study sought to evaluate the effects of disease induced by a live pathogen on plasma free AA flux and whole-body nitrogen (N ) utilization. Twenty gilts (BW 9.4 ± 0.9 kg) were surgically catheterized into the jugular vein, individually housed in metabolism crates, and feed-restricted (550 g/d). Intramuscular inoculation of a live field strain of porcine reproductive and respiratory syndrome virus (PRRSV ) was used to induce disease. Whole-body N-balance was conducted across 3 d both before PRRSV inoculation (PRRSV−) and also after PRRSV inoculation (PRRSV+). At the end of each N-balance period, a bolus dose of a labeled [U- 13 C, U- 15 N]-AA mixture (Ile, Leu, Lys, Met, Phe, Thr, Trp, Val, and Gln) was infused intravenously, followed by serial blood collection for measurement of isotopic enrichment. A double exponential model was fitted with plasma enrichment data for each pig and each AA, and equation parameters were used to estimate plasma free AA flux and pool size. Apparent ileal digestibility (AID ) of dietary N was determined using the slaughter technique and an indigestible marker. Blood chemistry, hematology, body temperature, and serum viremia indicated that PRRSV induced effective immune response in pigs ( P < 0.05). Challenge with PRRSV reduced the AID of N ( P < 0.05), but had no effect on apparent total tract digestibility of dietary energy ( P = 0.12). Plasma flux (µmol/kg BW/h) for Met and Thr was increased by PRRSV infection ( P < 0.05). A strong tendency of increased Val flux was observed in PRRSV+ pigs ( P = 0.06). Infection with PRRSV increased the pool size for Lys, Met, Thr, Trp, Leu, Val, and Gln ( P < 0.05). Collectively, these results suggest that PRRSV alters the utilization of dietary N and AA flux, as well as pool size, in growing pigs. The increase in Thr and Met flux in PRRSV+ pigs may be associated with enhanced utilization of these AA for the synthesis of immune system metabolites and increased catabolism of these AA. Thus, dietary Met, Thr, and Val requirements may increase in pigs infected with PRRSV, relative to the requirements for other AA.